2016
DOI: 10.1111/ane.12616
|View full text |Cite
|
Sign up to set email alerts
|

An updated review of Parkinson's disease genetics and clinicopathological correlations

Abstract: Knowledge regarding the pathophysiological basis of Parkinson's disease (PD) has been greatly expanded over the past two decades, with extraordinary contributions from the field of genetics. However, genetic classifications became complex, difficult to follow, and at times misleading, by placing well‐established monogenic forms of the disease along with others associated with risk loci, often ill characterized. The present paper summarizes the genetic, clinical, and neuropathological findings of the currently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
117
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(121 citation statements)
references
References 117 publications
(190 reference statements)
0
117
0
4
Order By: Relevance
“…On the other hand, increasing evidence has suggested that a genetic factor has a strong impact on the pathogenesis of PD. Indeed, in the past two decades, more than 20 genes have been identified as causal and/or risk genes for PD (Ferreira and Massano 2017). In particular, the implication of αSYN as a culprit of PD-linked neuropathology expanded enormously when the SNCA gene (PARK1), which encodes αSYN, was identified as the first PD-related gene (Polymeropoulos et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, increasing evidence has suggested that a genetic factor has a strong impact on the pathogenesis of PD. Indeed, in the past two decades, more than 20 genes have been identified as causal and/or risk genes for PD (Ferreira and Massano 2017). In particular, the implication of αSYN as a culprit of PD-linked neuropathology expanded enormously when the SNCA gene (PARK1), which encodes αSYN, was identified as the first PD-related gene (Polymeropoulos et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…α-Synuclein is a major PD-causative gene, and missense mutations and gene multiplication, or excessive phosphorylation of α-synuclein by GRK5 and GRK6 promotes its deposition in Lewy bodies. 2,7,8) EIF4G1 is ubiquitous and abundantly expressed in various tissues. It operates as a scaffold protein that interacts with many translation initiation factors.…”
Section: Resultsmentioning
confidence: 99%
“…Approximately 10% of PD is familial, and many causative genes have been identified. [1][2][3] However, the other 90% of PD occurs sporadically and its causes are poorly understood.…”
mentioning
confidence: 99%
“…For reasons of space, this review does not include new results on PD genes identified before 2012, where new results acquired in recent years have consolidated, expanded, and sometimes refuted previous knowledge. Readers are referred to broader previous reviews that summarize the knowledge in the field available at the time of their writing [16]. …”
Section: Introductionmentioning
confidence: 99%